Monitoring target reduction in hepatic venous pressure gradient during pharmacological therapy of portal hypertension: a close look at the evidence. Issue 1 (18th December 2003) - Thalheimer, U; Mela, M; Patch, D; Burroughs, A K
Abstract : Recurrent variceal bleeding is very frequent after variceal haemorrhage and pharmacological therapy is the first choice treatment. Recently, baseline and repeat measurements of hepatic venous pressure gradient (HVPG) have been considered necessary to optimally manage patients receiving pharmacological therapy so as to reduce the frequency of rebleeding. However, the clinical validity and applicability of monitoring for target HVPG reductions is not sufficiently proven and needs to be specifically evaluated in a prospective trial.